Sustainable Synthesis of Flavonoid Derivatives, QSAR Study and Insecticidal Activity against the Fall Armyworm, Spodoptera frugiperda (Lep.: Noctuidae) - Romanelli, Gustavo Pablo (2010)
A simple, clean, solvent-free preparation of flavones by the use of a silica-supported Preyssler heteropolyacid as reusable catalyst is described. High selectivity and very good yields (87−94%) were obtained in short reaction times (7−13 min). Bioassays for insecticidal activity against Spodoptera frugiperda were carried out with a set of flavones. Bioassays showed that some of the flavones had moderate insecticidal activity. Quantitative structure−activity relationships were established on the available data with the purpose of predicting the insecticidal activity of a number of structurally related flavones. A relationship between the molecular structure and biological activity is proposed.